Towards Shape Control of Metal Oxide Nanocrystals in Confined Molten Media. Issue 1 (30th April 2015) - Chen, Dennis P.; Fu, Jie; Skrabalak, Sara E.
Abstract: Spray synthesis is a robust route to compositionally complex materials as fine powders; however, the solid‐state synthetic conditions in most cases limit access to discrete nanoparticles with defined structural features. Yet, by maintaining a dynamic droplet phase through integration of molten salt chemistry, product formation can proceed in manners similar to lower temperature solution routes to nanomaterials. This Focus Review connects concepts from classical nucleation theory and molten salt chemistry to provide a framework for nanocrystal formation via aerosol‐assisted molten salt synthesis (AMSS). Examples of metal oxide nanocrystal formation by AMSS are surveyed and highlight how the spatial and temporal confinement of aerosol droplets limits crystal growth in molten media. Ultimately, we strive to provide practical guidelines, not limited to AMSS, towards the synthesis of compositionally complex materials as shape‐defined nanocrystals. Abstract : Everything under control : Spraying the way to shape‐controlled metal oxide nanocrystals, aerosol‐assisted molten salt synthesis provides spatially and temporally confined droplets for the crystallization of high‐quality nanomaterials.